A Randomized Controlled Trial of CBT+: A Clinician-Controlled, Just-In-Time, Adjunctive Intervention for Bulimia-Spectrum Disorders. Issue 3 (May 2023) - Juarascio, Adrienne S.; Presseller, Emily K.; Srivastava, Paakhi; Manasse, Stephanie M.; Forman, Evan M.
Cognitive Behavior Therapy (CBT) for bulimia nervosa (BN) requires patient skill utilization (use of treatment skills) and skill acquisition (successful skill use) for symptom improvement. Treatment outcomes are unsatisfactory, possibly due to poor skill acquisition and utilization by post-treatment. Just-in-time adaptive interventions (JITAIs), momentary interventions delivered at opportunities for skill practice, may improve skill acquisition and utilization. Participants ( N = 56 individuals with bulimia-spectrum eating disorders) completed electronic self-monitoring in CBT+ and received JITAIs or no JITAIs alongside 16 sessions of CBT. Feasibility, acceptability, target engagement, and treatment outcomes were evaluated. JITAIs demonstrated feasibility and acceptability. Treatment outcomes and target engagement did not differ between conditions. The lack of group differences in target engagement and treatment outcomes may be explained by skill use self-monitoring promoting skill utilization and acquisition or low statistical power. Our findings suggest that JITAIs are feasible and acceptable during CBT for BN and warrant additional study.